2005
DOI: 10.1300/j301v04n04_10
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Intensity of Root Colonization by Ericoid Mycorrhizal Fungi in Nursery Production of Blueberry Plants

Abstract: Ericoid mycorrhizal fungi (EMF) form symbiotic relationships with roots of blueberry plants providing increased access to nutrients from fertilizers and soil. A survey of commercial nursery plants produced from tissue culture and cuttings was conducted to determine when or if EMF colonize blueberry plants under nursery cultural methods. Although there were cultivar-specific differences, in general, colonization frequency (the percentage of plants colonized) and intensity (the percentage of root length with EMF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…A 5-g (fresh wt.) subsample of roots was washed from the pots, cleared and stained following procedures outlined in Scagel et al (2005a), and stored in lactoglycerin solution for later determination of EMF colonization. The remaining roots in the pots were washed, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 5-g (fresh wt.) subsample of roots was washed from the pots, cleared and stained following procedures outlined in Scagel et al (2005a), and stored in lactoglycerin solution for later determination of EMF colonization. The remaining roots in the pots were washed, dried, and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Ericoid mycorrhizal fungi (EMF) form symbiotic associations with roots of blueberry plants as well as other ericaceous plants and can increase their uptake of soil nutrients (Read, 1996). The association is common in both wild and cultivated blueberry plants and can occur during nursery production (Scagel et al, 2005a). In nurseries, however, colonization by EMF is often sporadic and can be quite low depending on cultivar and the method of plant production (Scagel et al, 2005a(Scagel et al, , 2005b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The other inocula resulted in mycorrhization frequency and intensity rates greater than those found for the azalea inoculum; G. pumila had a colonization frequency of 90.3% and intensity of 44.8%, while V. corymbosum had a frequency of 89.6% and intensity of 40.5%. Scagel et al (2005) reported that the low availability of propagules diminished the colonization potential of ericoid mycorrhizae, and it may be that this was the case for the Azalea sp. propagules.…”
Section: Degree Of Ericoid Mycorrhizal Colonization In Inoculated Culmentioning
confidence: 99%
“…The levels, however, vary with plantation age, soil nutrient content and Vaccinium cultivars [17,19,20]. Several authors attempted artificial inoculation of blueberries with selected strains of ericoid mycorrhizal fungi [18,21], but this did not always lead to an increased growth and/or fruit production.…”
Section: Introductionmentioning
confidence: 99%